The physics problem solving skills profile of high school students in elasticity material and the implementation of augmented reality book-assisted PBL model - Kirana Aureola Arzak; Binar Kurnia Prahani (Universitas PGRI Kanjuruhan Malang, 2023)
The research aims to analyze the physics PSS profile of high school students and the implementation of the AR book-assisted PBL model as a consideration in the use of media and learning models to support the high school students' PSS improvement. This is preliminary descriptive research without hypothesis testing with 154 high school students as participants. Descriptive methods of qualitative approach is employed to analyze through questionnaires and tests of assessment about PSS. This study revealed that the students’ PSS is still in the low level. This is evidenced by the students’ results of low category with a score range within 0 to 50. This study also found that students' interest in learning physics with AR (Augmented Reality) books-assisted have improved their PSS. It is concluded that the learning methods, as well as learning media, can affect students' PSS.